Indigenous Participation: Canada's Trade for Reconciliation - Serrano Burbano, Natalia (Revue Interventions économiques / Papers in Political Economy, 2026)
The constitutional recognition of reconciliation has paved the way for the integration of the Crown’s domestic obligations toward Indigenous peoples into Canada’s international commitments. In this context, trade policy has emerged as an additional avenue through which the national objective of reconciliation may be advanced. This paper examines the incorporation of Indigenous peoples’ rights and interests in six Canadian trade agreements concluded following the launch of Canada’s Progressive Trade Agenda. It analyzes the normative innovations introduced and evaluates the extent to which these agreements move beyond symbolic recognition toward meaningful participation. While the degree of integration varies across agreements, the findings suggest that Canadian trade policy increasingly reflects an effort to align international economic governance with the domestic imperative of reconciliation.